Aplikasi Teknologi Pengolahan Buah Tropis Menjadi Dodol, Juice, Manisan, Dan Pemasarannya Bagi Petani Muda Di Desa Baumata Timur - Lika Bernadina; Serman Nikolaus; Abraham R. Illu; Daniel Lay; Maria Sulastri (CV. Ulil Albab Corp, 2026)
Horticultural commodities, especially vegetables and fruits, are the mainstay commodities for the people of East Baumata Village. However, when the harvest of fruits and vegetables is abundant, if it is not followed by good handling, the fruits and vegetables will undergo a rotting process. The location of East Baumata Village is close to urban areas, and the potential of some of the land is quite fertile, providing a variety of tropical fruit plants that grow and produce. The condition of excess production has not received much attention from processing technology, which can produce processed products that can last a long time. This is due to limited input of business capital, knowledge, and skills. Young farmer groups, as drivers of change and agricultural entrepreneurs, play a vital role in developing the agricultural sector. Based on the potential and problems faced by members of the farmer group, it is deemed necessary to carry out training activities on tropical fruit processing technology (bananas, papaya, jackfruit, soursop, tomatoes, and starfruit) and post-harvest processing and marketing. In addition, it is also necessary to carry out technology transfer for the processing, packaging, and marketing of tropical fruits, as well as the formation of business groups as a source of income for young farmers in East Baumata Village. Therefore, on July 25, 2024, an extension activity and training were carried out to improve the knowledge and skills of young farmers in processing tropical fruits into dodol, juice, sweets, and their marketing (entrepreneurship in agriculture). The results of the evaluation of the assessment before and after the community service activity showed an increase in the knowledge and skills of the participants.